Circuit Mechanisms of L-DOPA-Induced Dyskinesia (LID) - Yang, Kai; Zhao, Xinyue; Wang, Changcai; Zeng, Cheng; Luo, Yan; Sun, Taolei (Frontiers in Neuroscience, 2021)
L-DOPA is the gold standard of treatment for Parkinson’s disease (PD). Although it alleviates some of the parkinsonian symptoms, long-term treatment induces L-DOPA induced dyskinesia (LID). Several theoretical models including the firing rate model, the firing pattern model and the ensemble model are proposed to explain the mechanisms of LID, but they all have some weakness. Extensive evidence for circuit mechanisms in driving LID symptoms has been presented. In addition, besides the striatum, other brain regions including the pallidal-subthalamic network, the motor cortex, the thalamus and the cerebellum are involved in the pathophysiology of LID. Although several drugs have been developed to treat LID, they all have serious side effects, a novel anti-dyskinetic drug is strongly needed, these require us to understand the circuit mechanism of LID more deeply.